Endodoncia no instrumentada vs convencional en dentición decidua: Revisión Bibliográfica - Bravo Bermeo, Gabriela del Cisne (2024)
The oral health of young children, especially in the primary dentition stage, is significantly challenged by carious lesions that can affect the dental pulp and lead to serious conditions such as irreversible pulpitis and pulp necrosis. In response, the standard treatment is conventional pulpectomy, which involves the instrumentation and filling of root canals. However, a noninstrumental approach to endodontics, using antibiotic pastes to sterilize and promote tissue repair without mechanical intervention, has gained increasing interest. The objective of this research project is to compare the protocols and effectiveness of non-instrumented endodontics versus conventional methods in pulpectomy of primary dentition. The methodology included a thorough review of the scientific literature, including systematic reviews and case studies, obtained from databases such as PubMed and Google Scholar. Strict inclusion and exclusion criteria were applied to ensure the reliability and quality of the data. When comparing the protocols used in both techniques, they are largely similar. However, the main difference is that conventional endodontics involves instrumentation of the root canals, while the non-instrumental technique relies solely on the application of antibiotic pastes placed at the entrance of each root canal. The results indicate that non-instrumented endodontics is as effective as conventional methods, with success rates of 80% for the resolution of pulpitis in non-instrumented cases and 75% for conventional treatments. The non-instrumented technique offers several advantages, including a significant reduction in invasiveness (90%) and shorter treatment time. As a result, it is considered a valuable and effective alternative to conventional methods, providing similar clinical outcomes with fewer complications and a less invasive approach